Favourable effects of Bacillus subtilis and Bacillus licheniformis on experimental periodontitis in rats - Messora, Michel R.; Pereira, Luciano J.; Foureaux, Renata; Oliveira, Luiz F.F.; Sordi, Caio G.; Alves, Ana J.N.; Napimoga, Marcelo H.; Nagata, Maria J.H. [UNESP]; Ervolino, Edilson [UNESP]; Furlaneto, Flávia A.C. (Elsevier, 2016)
Objectives The purposes of this study were to evaluate, in rats: i) the effects of Bacillus species on the development of experimental periodontitis (EP) via microtomographic, immunological and hematological assays (Experiment 1 - E1); ii) the effects of Bacillus species as adjuncts to scaling and root planing (SRP) for the treatment of EP via histomorphometric and immunohistochemical analyses (Experiment 2 - E2). Methods In E1, 24 rats were divided into groups C1 (control), PROB1, EP1 and EP-PROB1. In groups with EP, the mandibular first molar of each animal received a ligature for 14 days. In groups PROB1, animals received Bacillus species for 44 days, starting 30 days before EP induction in Group EP-PROB1. In E2, 24 rats were assigned to groups C2 (control), PROB2, EP-SRP2 and EP-SRP-PROB2. In groups with SRP, EP was induced as described in E1. The ligatures were removed after 14 days and SRP was performed. In groups PROB2, animals received Bacillus species for 15 days, starting after SRP in Group EP-SRP-PROB2. Results In E1, Group EP1 presented bone loss (BL) and eosinophil numbers greater than Group EP-PROB1 (P < 0.05). In Group EP-PROB1, the receptor activator of nuclear factor-kB ligand (RANKL)/osteoprotegerin (OPG) ratio was similar to that of groups without EP. In E2, Group EP-SRP-PROB2 presented fewer TRAP-positive osteoclasts, lower immunolabeling pattern for a proinflammatory cytokine and decreased BL and attachment loss than Group EP-SRP2 (P < 0.05). Conclusions Bacillus species supplementation provided a protective effect against BL and enhanced the effects of SRP in the treatment of EP in rats.
Keywords: Periodontitis; Probiotics; Rats; Root planing